PENGARUH MANAJEMEN MODAL DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI INTERVENING - Noer Azizah Fitriyanti; Nugroho Mardi Wibowo; C. Sri Hartati (CV. ALIM'SPUBLISHING, 2023)
The purpose of this research is to find out and analyze the effect of capital management and leverage on firm value through profitability. This research belongs to the type of associative research, while the research approach uses quantitative. The population is Food and Beverage manufacturing sector companies listed on the IDX for 2018-2021. The sampling technique with purposive sampling, obtained a sample of 13 companies. Data analysis in this study uses Partial Least Square (PLS). The results showed that capital management had a significant negative effect on the profitability of Food and Beverage manufacturing companies, Leverage had a non-significant negative effect on the profitability of Food and Beverage manufacturing companies, Capital management had a significant positive effect on the value of Food and Beverage manufacturing companies, Leverage had a significant positive effect on Company value Food and Beverage manufacturing, Profitability has a significant effect on the value of Food and Beverage manufacturing companies. Capital management has a significant negative effect on firm value through profitability in Food and Beverage manufacturing companies. Leverage has no significant negative effect on firm value through profitability in Food and Beverage manufacturing companies.